Are tourism strategies responsive to critical events? - Marot, Naja (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2022)
In 2020, the COVID-19 pandemic brought tourism to an abrupt halt. Supply-side stake-holders suddenly found themselves in a lockdown with unusable assets, unprofi table investments and jobs in jeopardy. Using qualitative research, we take a closer look at how they dealt with this unprecedented crisis in the Slovenian urban destinations of Ljubljana and Maribor. Our results show that existing policy and strategy mechanisms did not equip the supply-side stakeholders to tackle the pandemic challenges. However, both institutional ad hoc responses were quick and to some extent adequate.
Keywords: COVID-19; Ljubljana; Maribor; mesta; pandemics; pandemije; strategy; tourism; towbs; turizem